Neutrophil phagocytosis and respiratory burst activity of dairy cows during the transition period and early lactation - Žekić-Stošić, Marina; Kanački, Zdenko; Stojanović, Dragica; Bugarski, Dejan; Lazarević, Miodrag; Milovanovic, Aleksandar; Masic, Aleksandar (The Journal of Infection in Developing Countries, 2018)
Introduction: Hormonal and metabolic changes, as well as energy imbalance, can affect health, production and reproductive performance of dairy cows. In the present study, we evaluated phagocytosis and respiratory burst neutrophil activity during the transition period and early lactation and compared it with biochemical and hematological parameters in dairy cows. Methodology: Simmental cows (n = 21) were enrolled in the study. Whole blood samples were collected weekly from 3 weeks pre- calving until 6 weeks post calving. Basic metabolic and blood parameters were assessed by routine laboratory analyses, while neutrophil functions were analyzed by commercial test kits. Results: Optimal neutrophil response was observed pre and post calving. The highest value was recorded in the 6th week after calving (89.54 ± 7.61%) and being significantly higher (p < 0.01) as compared to values recorded at two and one week before and one week after calving. The percentage of activated neutrophils was high during the entire study period: from 70.80 ± 5.22% at the beginning of the study to 89.54 ± 7.61% at the end of the study. During the study period, production of Reactive Oxidative Species by neutrophils was positively correlated with β-hydroxybutyrat and non-esterified fatty acids values (0.454** and 0.423**, respectively) and calcium levels (0.164* and 0.212**, respectively). Conclusions: The most prominent changes in all parameters had no influence on phagocytic and respiratory burst activity of neutrophils. Neutrophil function is preserved at the optimal level during the transition period and early lactation in Simmental cows.